2023
DOI: 10.1002/advs.202207253
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Diethanolamine and Polyethyleneimine with Enhanced CO2 Capture Capacity from Air

Abstract: Supported polyethyleneimine (PEI) adsorbent is one of the most promising commercial direct air capture (DAC) adsorbents with a long research history since 2002. Although great efforts have been input, there are still limited improvements for this material in its CO2 capacity and adsorption kinetics under ultradilute conditions. Supported PEI also suffers significantly reduced adsorption capacities when working at sub‐ambient temperatures. This study reports that mixing diethanolamine (DEA) into supported PEI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The activation barrier for CO 2 adsorption and/or proton transfer may also play a more significant role at these lower temperatures. We contend that this technique will be particularly useful for studying an array of materials and additives for understanding and optimizing sub-ambient capture processes. , We turn now to studying changes in polymer mobility under a variety of simulated DAC conditions, namely, 100 sccm of 400 ppm CO 2 in N 2 at different RH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation barrier for CO 2 adsorption and/or proton transfer may also play a more significant role at these lower temperatures. We contend that this technique will be particularly useful for studying an array of materials and additives for understanding and optimizing sub-ambient capture processes. , We turn now to studying changes in polymer mobility under a variety of simulated DAC conditions, namely, 100 sccm of 400 ppm CO 2 in N 2 at different RH.…”
Section: Resultsmentioning
confidence: 99%
“…7 Indeed, a diverse array of recent work studying nonvolatile aminopolymers loaded onto mesoporous oxide composites is driving extraordinary advances in the field. 8−14 However, certain fundamental knowledge gaps remain that will influence how these and similar materials are employed over long cycle times, 15−17 in different environments, 18,19 and within different operational design constraints in real-world DAC systems. 20 One such knowledge gap involves structure−property− performance relationships associated with polymer segmental mobility in confinement.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research focuses on the co-impregnation of additives with amines, 18,27,[35][36][37][38] by which the diffusion limitation of CO 2 can be alleviated due to the inter-actions between the amines and the additives. Jones's group conducted a study wherein various additives were impregnated with polyethyleneimine (PEI) into SBA-15.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, from the earliest studies on these materials, the mobility of the supported amines within the mesopores of the support was recognized as an important factor. Further research on those materials aimed to improve their CO 2 uptake properties by varying pore sizes, leaving behind surfactants (e.g., CTAB) around pore walls, using additives (e.g., PEG) or smaller, molecular amines (e.g., diethanolamine), , and using combinations of grafted amines together with physically impregnated amines. , Researchers observed varied gas capture performance under these different circumstances. In many cases, the authors suggested that a more favorable distribution and motions of amines were the main driving forces behind the improved performance.…”
Section: Introductionmentioning
confidence: 99%